2002
DOI: 10.1074/jbc.m108753200
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Peptide Responsible for Amyloid Fibril Formation of β2-Microglobulin byAchromobacter Protease I

Abstract: To obtain insight into the mechanism of amyloid fibril formation from ␤ 2 -microglobulin (␤2-m), we prepared a series of peptide fragments using a lysine-specific protease from Achromobacter lyticus and examined their ability to form amyloid fibrils at pH 2.5. Among the nine peptides prepared by the digestion, the peptide Ser 20 -Lys 41 (K3) spontaneously formed amyloid fibrils, confirmed by thioflavin T binding and electron microscopy. The fibrils composed of K3 peptide induced fibril formation of intact ␤2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
141
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 33 publications
20
141
0
Order By: Relevance
“…Two peptides (residues 21-40, the so-called K3 peptide, and residues 59-71), which overlap with the regions that are strongly exchange broadened in the pH 3.6 intermediate, were reported to self-associate in Vitro. 22,23 The two -strands (residues 21-28 and 33-40) observed in amyloid fibrils of the K3 peptide 24 match the two minima in the H/D exchange profile (Figure 2), suggesting that amyloid fibrils of full-length b2m also contain two -strands in this region.We demonstrated that signals of partially unfolded intermediate ensembles broadened due to conformational exchange can be structurally characterized using direct carbon-detected NMR experiments. Comparison between the structural and dynamic properties of the amyloid intermediate of b2m with H/D exchange measurements on amyloid fibrils revealed a close relationship between the conformational properties of the metastable partially unfolded precursor and the -sheet-rich insoluble aggregates of a diseaserelevant protein that assumes a rigid 3D fold in its native state.…”
mentioning
confidence: 68%
“…Two peptides (residues 21-40, the so-called K3 peptide, and residues 59-71), which overlap with the regions that are strongly exchange broadened in the pH 3.6 intermediate, were reported to self-associate in Vitro. 22,23 The two -strands (residues 21-28 and 33-40) observed in amyloid fibrils of the K3 peptide 24 match the two minima in the H/D exchange profile (Figure 2), suggesting that amyloid fibrils of full-length b2m also contain two -strands in this region.We demonstrated that signals of partially unfolded intermediate ensembles broadened due to conformational exchange can be structurally characterized using direct carbon-detected NMR experiments. Comparison between the structural and dynamic properties of the amyloid intermediate of b2m with H/D exchange measurements on amyloid fibrils revealed a close relationship between the conformational properties of the metastable partially unfolded precursor and the -sheet-rich insoluble aggregates of a diseaserelevant protein that assumes a rigid 3D fold in its native state.…”
mentioning
confidence: 68%
“…We found that a 22-residue K3 peptide, Ser 20 -Lys 41 ( Fig. 1), obtained by digestion of ␤ 2 m with Acromobacter protease I, forms amyloid fibrils (30). Recently, we further identified an 11-residue peptide, Asn 21 -His 31 , in the K3 region that also forms amyloid fibrils (42).…”
mentioning
confidence: 95%
“…Recombinant ␤ 2 m and K3 Peptide-Recombinant human ␤ 2 m was expressed in the methylotrophic yeast, Pichia pastoris, and purified as described (29,30). Three fractions with 6 (Glu-Ala-Glu-Ala-Tyr-Val-), 4 (Glu-Ala-Tyr-Val-), and 1 (Val-) additional amino acid residues added to the N-terminal (Leu) of intact ␤ 2 m were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…K3 was obtained by digestion of ␤2-m with lysyl endopeptidase (Achromobacter protease I) as reported previously (16).…”
Section: Methodsmentioning
confidence: 99%